電腦輔助教學與個別教學結合: 電腦輔助教學課堂應用初探 Computer-Assisted Instruction Under the Management of Individualized Instruction: A Classroom Management Approach of CAI - Sunny S. J. Lin (Jiàoyù zīliào yǔ túshūguǎn xué, 1988)
無 First reviews the development of Computer. Assisted Instruction (CAI) in Taiwan. This study describes the training of teachers from different levels of schools to design CAI coursewares, and the planning of CAI courseware bank possesses 2,000 supplemental coursewares. Some CAI's c1assroom application system should be carefully established to prevent the easy abuse of a CAI courseware as an instructional plan. The study also claims to steer CAI in our elemantary and secondary education could rely on the mastery learning as the instructional plan. In this case, CAI must limit its role as the formative test and remedial material only. In the higher education , the Keller's Personalized System of Instruction could be an effective c1assroom management system. Therefore, CAI will offer study guide and formative test only. Using these 2 instructional system may enhance student's achievement , and speed up the learning rate at the same time. Combining with individualized instruction and CAI will be one of the most workable approach in current c1assroom . The author sets up an experiment 10 varify their effectiveness and efficiency in the near future.